Medical Physiology : Principles for clinical medicine - Rhoades, Rodney A.; Bell, David R. (Philadelphia : Wolters Kluwer, 2013)
Medical Physiology presents physiological concepts essential to clinical medicine, along with just the right amount of explanatory datail.
Contents Part I: Celular Physiology Part II: Neuromuscular Physiology Part III: Blood anda Immunology Part IV. Cardiovascular Physiology Part V. Respiratory Physiology y otros cinco más...
Incluye appendix ; glossary ; index
Keywords: FISIOLOGÍA HUMANA; REPRODUCCIÓN HUMANA; MEDICAL PHYSIOLOGY